Variation in Chemicals and Antimicrobial Activities Of Nicotiana Glauca Graham (Bangladesh Journal of Botany, 2023)
Nicotiana glauca was recorded as one of the invasive plant species which is dramatically spreading in many countries. Extracts of methanol, hexane, acetone, ethanol and petroleum ether of leaves of Nicotiana glauca obtained from seven locations were screened for their antimicrobial activities against Klebsiella oxytoca, Shigella sp., Staphylococcus aureus, Micrococcus luteus and Candida albicans. Forty seven chemical compounds were characterized and vitamins B1, B12, B2 and folic acid were also found. All studied locations had toxic chemicals to human namely anabasine. The similarity index among locations was about 69.01% and the most dominant compound were 2-Pentanone, 4-hydroxy-4-methyl, 1,3-Dioxolane- 2-methanol, 2,4-dimethyl and 2-Acetoxyisobutyryl chloride. Interestingly, the plant had anabasine and showed low antimicrobial effect against specific human pathogens. Data of permanent quadrats showed the plant spread in a progressive manner.Bangladesh J. Bot. 52(2): 403-410, 2023 (June)